Sandwiched Plate Vibration Analysis with Open and Closed Lattice Cell Core - Raad, Hussam; Njim, Emad Kadum; Jweeg, Muhsin J.; Al-Waily, Muhannad (Physics and Chemistry of Solid State, 2023)
This work attempts to replace the sandwich core's traditional shape and material with a cellular pattern, where the cells have a regular shape, distribution, and size. The contribution of this paper is to design two structures, one open-celled and the other closed, and to evaluate the performance of sandwich plates with lattice cell core as it is used for many industrial applications, particularly in automobile engineering. The new theoretical formulations are constructed for two structures to find the free vibration characteristics. The results of the new design are compared with the traditional shape. Derivation of equations to predict mechanical properties based on relative density with the chosen shapes, specific vibration equation of three-layer sandwich plate, and substitution by equation using excel sheet. Results are promising, and the effectiveness of cellular pattern theoretical analysis estimation. Limitations and error rates for the mechanical properties come through the empirical equations, and their ratio to the relative density values are higher depending on the behavior of the core material. Findings reveal, with open cell decrease in modulus of elasticity by (PLA: -90.4%) and (TPU: -90.4%), increases natural frequency by (PLA: 44.5%) and (TPU: 46.4%), as for closed-cell decreases in the modulus of elasticity by (PLA: -66.9%) and (TPU: -64.4%), increases natural frequency by (PLA: 36%) and (TPU: 37.7%). Converting a solid substance or replacing a foam form with a cellular pattern is one way to better performance and save weight through the selected cell pattern in absorbing the energy of the vibration wave.